2019
DOI: 10.2134/jeq2018.12.0430
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Concentrations in New Zealand Wheat: Effect of Cultivar Type, Soil Properties, and Crop Management

Abstract: Wheat (Triticum aestivum L.) grain is a contributing source of dietary Cd in New Zealand, but despite this, there is a dearth of information on Cd concentrations in wheat and the factors that affect uptake. We measured Cd concentrations in 12 wheat cultivars grown in field sites across New Zealand and also assessed the soil, plant, and crop factors that have been reported to affect Cd uptake. We found there was a wide range in grain Cd concentrations (0.004 to 0.205 mg kg−1 fresh weight [FW]). The overall mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…There are several soil and crop management factors that also have a significant impact on solubility of Cd in soil and root uptake such as soil pH, cropping systems, liming, soil salinity, phytoavailability of Zn in soil, the levels of nitrogen and P fertilization and plant genotype (Mench 1998;Sheppard et al 2009;McLaughlin et al 2021). It is commonly observed that the soil Cd concentration shows a poor association with the plant Cd concentration in several crops such as wheat, potato and rice (McLaughlin et al 1997;Li and Zhou 2019;Gray et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are several soil and crop management factors that also have a significant impact on solubility of Cd in soil and root uptake such as soil pH, cropping systems, liming, soil salinity, phytoavailability of Zn in soil, the levels of nitrogen and P fertilization and plant genotype (Mench 1998;Sheppard et al 2009;McLaughlin et al 2021). It is commonly observed that the soil Cd concentration shows a poor association with the plant Cd concentration in several crops such as wheat, potato and rice (McLaughlin et al 1997;Li and Zhou 2019;Gray et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of Cd in grains (mean of 0.92 mg kg À1 ) was evidence that when wheat grew exposed to half the permitted values (1.5 mg kg À1 ), it did not result in toxic effects on plants; however, grains could have toxic levels of Cd for animals and humans. Furthermore, Gray et al (2019) evidence that variations in Cd uptake capacity might be observed depending on the wheat cultivars. Also, differential Cd uptake capacity among the wheat cultivars causes differences in Cd accumulation in wheat derivates, i.e., flour, consequently presenting Cd levels that disagree with national standards.…”
Section: Resultsmentioning
confidence: 90%
“…Wheat cultivation on soils contaminated with Cd and Pb is well-reported: Gray et al (2019) studied the effects of the cultivar type, soil properties, and crop management in New Zealand-contaminated soils. Wu et al (2020) observed Pb uptake to grains, making predictions for the translocation of Pb for different wheat organs in different types of China soils.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of Cd in cultivated soils ranged from 0.11 to 6.37 mg kg −1 , whereas in the background soil it ranged from 0.02 to 1.99 mg kg −1 in the Sydney region (Gray et al, 2019). The ANZ environmental investigation guideline for soil Cd is 3 mg kg −1 (Siddique et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological urban soil investigation level is 3 mg kg −1 although background Cd in soil is 1 mg kg −1 (Kandic et al, 2019). Moreover, wheat grain Cd concentrations exceed the Australian and New Zealand food standards for Cd when it is grown in soil with 0.6 mg Cd kg −1 soil (Gray et al, 2019). The low-Cd accumulating wheat cultivars with high macro-and micro-nutrients contents in plant biomass are the best way to diminish Cd concentration in wheat grain.…”
Section: Introductionmentioning
confidence: 99%